Semantic efforts in phenotypic interpretation Co-verbal and opposites (Journal of the College of Basic Education, 2022)
Praise be to God, who favors His servants with His abundant grace, and bestows upon them His complete grace, the creatorCreation with His power, perfecting His verses with His wisdom, who created the types of creation, and favored some of them over othersgrades.And after:The Muslim's keenness to clarify the meanings of the Holy Qur'an and the creativity in it led him toDiversifying his studies of the Holy Qur’an, so these studies varied in quantity and quality, and one of the important areasRelated to the study of the Holy Quran: semantic studies.This research was devoted to dealing with an aspect of the semantic efforts in one of the books of self-examinationIt is the phenomenological interpretation of the late Al-Fani Fati, and I have dealt with his linguistic and grammatical efforts inMy doctoral thesis, so I decided to deal with his semantic efforts in this research, which I called (effortsSemantics in the phenotypic interpretation - verbal joint and opposites).